Power system transient stability enhancement - Keh, Soon Heng (Nanyang Technological University, 2022)
This report analyses what is power system transient stability enhancement, and how it works, and review two popular common technologies used, this also includes two other possible improvement or implementation to further enhance the existing technologies. To understand how it works we will need to first understand how a power system works with the help of a simplified power model known as the Single Machine to Infinite Bus and make used of the simulation software “MATLAB” to build and run the stimulation models. Last but not least, we will review and conclude our results from stimulation models and analyses by comparing results and suggest what could be done for future recommendations.